Highly active phosphite gold(I) catalysts for intramolecular hydroalkoxylation, enyne cyclization and furanyne cyclization - Maria Camila Blanco Jaimes (2014)
New and highly active mononuclear phosphite gold(I) catalysts are described. Turn-over numbers up to 37 000 for the furanyne reaction and up to 28 000 000 for the two-fold hydroalkoxylation of alkynes are reported.